Social protection during conflict: reflections on Tigray - Sabates-Wheeler, Rachel; Lind, Jeremy (Institute of Development Studies, 2021)
Conflict and an ensuing humanitarian crisis in Ethiopia’s northern Tigray region have led to substantial population displacement and threaten the lives and livelihoods of millions. In a situation where rising needs outstripped preliminary humanitarian responses and where safety net programmes that were purposed for shock-response have been curtailed or stopped functioning altogether, what are the […]
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

Conflict is the new ‘hazard’ on the social protection block - Sabates-Wheeler, Rachel; Slater, Rachel; Lind, Jeremy; Harvey, Paul; Oosterhoff, Pauline; Faith, Becky; Naess, Lars Otto; Selby, Jan; Roberts, Tony; Longhurst, Daniel; Rohwerder, Brigitte; Collyer, Michael; et al. (Institute of Development Studies, 2021)
Although social protection has the potential to address crises in different ways, the evidence base is thematically and geographically patchy. The Foreign, Commonwealth and Development Office-funded (FCDO)-funded Better Assistance in Crises (BASIC) Research programme aims to inform policy and programming on effective social assistance in situations of crisis, including those experiencing climate-related shocks and stressors, protracted conflict and forced displacement.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social